(untitled) (Nóema, 2016)
The text focuses on the status of sciences, starting from the psychiatric discipline, related to the crisis that from the 60s to today has threatened his epistemological presuppositions. Not otherwise, the other sciences, on the the wave of progress and technological development, end up reaching increasingly important results, paying the price of losing the condition and the aim of research and knowledge.